The Reliability and Validity of the Clinical Perfectionism Questionnaire in Eating Disorder and Community Samples - Egan, Sarah; Shafran, R.; Lee, M.; Fairburn, C.; Cooper, Z.; Doll, H.; Palmer, R.; Watson, H. (Cambridge University Press, 2016)
Background: Clinical perfectionism is a risk and maintaining factor for anxiety disorders, depression and eating disorders. Aims: The aim was to examine the psychometric properties of the 12-item Clinical Perfectionism Questionnaire (CPQ). Method: The research involved two samples. Study 1 comprised a nonclinical sample (n = 206) recruited via the internet. Study 2 comprised individuals in treatment for an eating disorder (n = 129) and a community sample (n = 80). Results: Study 1 factor analysis results indicated a two-factor structure. The CPQ had strong correlations with measures of perfectionism and psychopathology, acceptable internal consistency, and discriminative and incremental validity. The results of Study 2 suggested the same two-factor structure, acceptable internal consistency, and construct validity, with the CPQ discriminating between the eating disorder and control groups. Readability was assessed as a US grade 4 reading level (student age range 9–10 years). Conclusions: The findings provide evidence for the reliability and validity of the CPQ in a clinical eating disorder and two separate community samples. Although further research is required the CPQ has promising evidence as a reliable and valid measure of clinical perfectionism.